THE USE OF THE FRAYER MODEL TO INCREASE THE STUDENT'S VOCABULARY MASTERY IN UMI MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2026)
AbstractThis research aims to discover the influences of using the Frayer Model to increase the student's vocabulary mastery in 22 generations of the English Education Study Program in UMI Makassar and to know the difficulties in using the Frayer Model to increase students' vocabulary mastery faced by the 22 generations of the English Education Study Program in UMI Makassar. The research was experimental with quantitative one using a one-group with pretest-posttest design which consists of one specified group up to 12 students from 22 generations in UMI Makassar. The research data consisted of a pre-test and a post-test to assess the samples' quality and uniformity and also examine the performance, and determine how the treatment presence influenced learning of vocabulary mastery. The treatment was carried out in two meetings to determine the outcome of applying the Frayer Model to teach vocabulary. The result of this research showed that the mean score of the pre-test was 66.66, and the mean score of the post-test was 87.22. The result of t-value = 3.458 with the Sig. (2-tailed) = 0.000. And t-table of 0.05 (5%) as the significance level is 2.201 with 11 the degree of freedom (df). It can be found that t-value = 3.458 > t-table = 2.201. It means that the use of the Frayer Model during the research can effectively influence the students' vocabulary mastery. One of the difficulties that occurred in this research was that most of the students used Indonesian to fill in the Frayer chart because they were still confused about arranging the use of words in English. The other was they are still lacking in the mastery of vocabulary, but the influences of using the Frayer Model can make students think more critically when filling in the Frayer chart.